Children’s Plays and Illustrations: Embodiment Resources for Reading Practices - Pinto, Isabel (2014)
This paper aims at enlightening the role played by illustrations in the reading of plays as means to an improved meaning assessment. Looking at the pictures, students are asked to perform, through improvisation, what is depicted in the image. This way, they engage in a mode of embodied reading that drives a new range of clues for constructing textual meaning. Students not only rely on internal processes to elaborate on the text’s meaning but attain to bodily experiences to achieve a personal understanding of the plot, thus arguing for the relevance of “embodied cognition” and “embodied pedagogy” as core concepts.